If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Y + 3)(y + -12) = 0 Reorder the terms: (3 + Y)(y + -12) = 0 Reorder the terms: (3 + Y)(-12 + y) = 0 Multiply (3 + Y) * (-12 + y) (3(-12 + y) + Y(-12 + y)) = 0 ((-12 * 3 + y * 3) + Y(-12 + y)) = 0 ((-36 + 3y) + Y(-12 + y)) = 0 (-36 + 3y + (-12 * Y + y * Y)) = 0 (-36 + 3y + (-12Y + yY)) = 0 Reorder the terms: (-36 + -12Y + 3y + yY) = 0 (-36 + -12Y + 3y + yY) = 0 Solving -36 + -12Y + 3y + yY = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '36' to each side of the equation. -36 + -12Y + 3y + 36 + yY = 0 + 36 Reorder the terms: -36 + 36 + -12Y + 3y + yY = 0 + 36 Combine like terms: -36 + 36 = 0 0 + -12Y + 3y + yY = 0 + 36 -12Y + 3y + yY = 0 + 36 Combine like terms: 0 + 36 = 36 -12Y + 3y + yY = 36 Add '-3y' to each side of the equation. -12Y + 3y + -3y + yY = 36 + -3y Combine like terms: 3y + -3y = 0 -12Y + 0 + yY = 36 + -3y -12Y + yY = 36 + -3y Reorder the terms: -36 + -12Y + 3y + yY = 36 + -3y + -36 + 3y Reorder the terms: -36 + -12Y + 3y + yY = 36 + -36 + -3y + 3y Combine like terms: 36 + -36 = 0 -36 + -12Y + 3y + yY = 0 + -3y + 3y -36 + -12Y + 3y + yY = -3y + 3y Combine like terms: -3y + 3y = 0 -36 + -12Y + 3y + yY = 0 The solution to this equation could not be determined.
| x(x+4)=x^2+4 | | 24=g/2-14 | | 5k=0.35 | | y=6x^2+5x+7 | | 3(x-3)+3(x-3)+(x+3)+(x+3)=84 | | 2g=0.6 | | 4x+6x-8=1+7x | | 14f-66=5f+87 | | 2g+97=5g-98 | | 4x(2)=28 | | 8f+50=57f-97 | | 13z+13=23z-67 | | -(5/2)x+(7/3)=-(3/4)x-4 | | 40q+99=72q-93 | | 4b+41=7b-1 | | y=6x^2+7x+10 | | 4y+29=6y-71 | | 14j+68=56j-100 | | (6x^2+15x+4)/(x+2) | | 26x+16=51x-34 | | 8b+49=13b-91 | | 4y+3/5=3/4 | | 189/4 | | Y=8X^2-X-6 | | fx(6)=4x-2 | | 8a-24z= | | -1/4=189.5 | | 7x^2+5x-h=0 | | 4y=6/9 | | -2-2=-6+x | | 18x+6-21-2x= | | F(X)=-6X-3+X(3X-7) |